Fatores sociodemográficos, clínicos e terapêuticos associados a fraturas maxilofaciais em uma população brasileira : estudo transversal em hospital terciário no período entre 2006 e 2015 - Sá, Carlos Diego Lopes (2016)
Objective: Trauma is recognized as a worldwide public health issue with maxillofacial fractures being commonly seen in the most vulnerable populations of undeveloped countries. Thus, the present study aimed to determine the epidemiological profile of oral and maxillofacial trauma patients of a tertiary hospital in the northeast region of Brazil from 2006 to 2015. Materials and methods: A retrospective study was conducted and the data obtained from the patients records were grouped into independent variables (socio-demographic, etiological and therapeutic data) and outcome variables (fracture occurrence). Results: A total 338 patients were identified, most of them male (p<0,001), aged between 21 to 30 years (p<0,001), bearing mainly single fractures (p<0,001) and not wearing safety devices (p<0,001). No statically significant difference was seen related with the geographical place of origin (p=0,644), but motorcycle accidents was significant (p<0,001). Mandibular and orbital-zygomatic complex fractures were prevalent (p<0,001), specifically mandibular angle fractures (p<0,001). The following were also prevalent: open surgical treatment (p<0,001), in the first 14 days following the trauma, by means of an intra-oral approach (p<0,001) and nasotracheal intubation (p<0,001). Conclusion: maxillofacial fractures were significantly associated with socio-demographic, etiological and therapeutic factors.